2014
DOI: 10.1177/0891988714524628
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Complaints Correlate With Depression Rather Than Concurrent Objective Cognitive Impairment in the Successful Aging Evaluation Baseline Sample

Abstract: Objective Whether subjective cognitive complaints are suggestive of depression or concurrent cognitive impairment in older adults without dementia remains unclear. The current study examined this question in a large (N=1,000), randomly-selected community-based sample of adults ages 51-99 without a formal diagnosis of dementia (Successful AGing Evaluation study-SAGE). Methods The modified Telephone Interview for Cognitive Status (TICS-m) measured objective cognitive function, the Cognitive Failures Questionna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
92
4
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 113 publications
(115 citation statements)
references
References 44 publications
17
92
4
2
Order By: Relevance
“…In contrast, SCD is not significantly associated with performance on objective tests of cognition when adjusting for demographics and symptoms of depression. These results in Hispanic older adults replicate previous findings in non-Hispanic Whites [8, 9] and support the conclusion that SCD is more indicative of symptoms of depression than concurrent cognitive function in older Hispanics who report cognitive complaints to their primary care physician [5, 1921]. The findings are also consistent with previous studies that have shown that subjective memory complaints are associated with sub-syndromal or sub-clinical depression in community-dwelling older adults [19, 22].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In contrast, SCD is not significantly associated with performance on objective tests of cognition when adjusting for demographics and symptoms of depression. These results in Hispanic older adults replicate previous findings in non-Hispanic Whites [8, 9] and support the conclusion that SCD is more indicative of symptoms of depression than concurrent cognitive function in older Hispanics who report cognitive complaints to their primary care physician [5, 1921]. The findings are also consistent with previous studies that have shown that subjective memory complaints are associated with sub-syndromal or sub-clinical depression in community-dwelling older adults [19, 22].…”
Section: Discussionsupporting
confidence: 90%
“…The purpose of this study was to assess linear relationships between SCD, cognition, and symptoms of depression rather than establishing SCD diagnosis or separating the sample into diagnostic groups. We hypothesized that, consistent with our prior findings in non-Hispanic Whites [8, 9], SCD would be more closely associated with symptoms of depression than with objective cognitive test performance.…”
Section: Introductionmentioning
confidence: 60%
“…The present results corroborate and extend previous results. A recent study on healthy individuals [26] found a significant association between subjective cognitive complaints and depression symptoms, while there was no correlation between subjective cognitive complaints and objective cognitive functioning once controlling for depression. Bayard et al [18] reported similar results in a group of patients with narcolepsy.…”
Section: Discussionmentioning
confidence: 91%
“…Because patients with narcolepsy often complain about attention deficits in everyday situations, insight into the emotional, cognitive, and clinical factors contributing to the subjectively perceived attention deficits is of major importance for clinicians involved in patients' counselling, and in choosing the appropriate treatment. It has been shown that subjective cognitive complaints may be more likely related to depression symptoms than to current cognitive functioning [26]. It was therefore hypothesised that depression, more than objective cognitive impairments, may play a role into the subjectively perceived attention deficits of patients with narcolepsy.…”
Section: Introductionmentioning
confidence: 98%
“…Depression and depressive symptomatology have been established as a risk factor for cognitive decline in older adults (Shahnawaz et al, 2013;Zlatar, Moore, Palmer, Thompson, & Jeste, 2014). Previous studies have shown that depressive symptomatology correlated negatively with general cognitive status as measured by the Montreal Cognitive Assessment (MoCA) in both the community and clinical populations (Baer et al, 2013;Blair et al, 2016).…”
Section: Introductionmentioning
confidence: 96%